Synthesis and electrochemical performance of micro-sized Li-rich layered cathode material for Lithium-ion batteries. (1st September 2016) - Pan, Lingchao; Xia, Yonggao; Qiu, Bao; Zhao, Hu; Guo, Haocheng; Jia, Kai; Gu, Qingwen; Liu, Zhaoping
Highlights: Micron Li-rich oxides have been synthesized by a new two-step method. Micron particles result in high pellet density and good cycling performance. High capacity of the micron Li-rich oxide was achieved after Na2 S2 O8 treatment. Abstract: Li-rich layered oxides with micro-sized primary particles usually exhibit higher pellet density and better cycling performance. However, it is often at the expense of high reversible capacity. Here, we reported a simple strategy through a new chemical lithiation with micro-sized spinel-precursors and Na2 S2 O8 surface treatment to obtain micro-sized particles in the Li-rich Li1.172 Ni0.135 Co0.135 Mn0.539 O2 oxide without compromising its discharge capacity (260 mAh/g at 0.1C). Benefited from its larger particles and lower specific surface area, the obtained micron Li-rich layered material manifests its higher pellet density (3.18 g/cm 3 ) and better cycling performance in comparison with the nano-sized Li-rich layered material. After 100 cycles at 0.1 C, it can still deliver a capacity of 192 mAh/g with retention of 74%, much higher than 167 mAh/g with retention of 67% of the nano-sized sample. Moreover, the micron Li-rich layered material also exhibits good rate performance with a capacity of 174 mAh/g at 2C benefited from the 3D Li + insertion/extraction channel of its surface spinel content. These results may provide a new insight on improving pellet density of high-performance Li-rich layered cathode materials.